STATUTORY REQUIREMENTS AS TO FORM AND CONTENT OF EXECUTORS' REPORTS TO COURTS. - Hay, Leon E. (The Accounting Review, 1955)
Abstract In the November, 1945, issue of the "Journal of Accountancy," Emanuel Sax described "An Improved Form of Summary Statement for Fiduciaries." In that article Dr. Saxe pointed out many deficiencies in the charge and discharge form of executors' account in use in the Surrogate's Court of the County of New York. Although the charge and discharge statement has been presented to three generations of accounting students by almost every text published in the United States in the last six decades as the "customary" form or the "most suitable" form of executors' report, Dr. Saxe is one of the few writers who has devoted any critical attention to it or to other forms of executors' reports. Every state has certain statutory provisions pertaining to reports of executors and administrators. Additionally, statutes are usually implemented by rules and orders of the courts of jurisdiction. No matter how peculiar some of these legal restrictions may seem to an accountant and no matter how superior he may feel another form of report to be, he must prepare executor's reports in the form required by the statutes and court of jurisdiction.